Handbook of research on service-oriented systems and non-functional properties future directions - Reiff-Marganiec, Stephan.; Tilly, Marcel, 1971- (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2011)
"This book unites different approaches and methods used to describe, map, and use non-functional properties and service level agreements"--Provided by publisher.